We Exist: Intersectional In/Visibility in Bisexuality & Disability - Kate Caldwell (Disability Studies Quarterly, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The intersection of theories of disability and bisexuality is unexplored, yet both are identities rendered in/visible by paternalistic environments where individual and political identities are defined by oppositional binaries and vulnerable to compulsory citizenship. The development of such identities can be better understood by using a bisexual approach to inform theories of disability and a disability approach to inform theories of sexuality inclusive of bisexuality. Common themes that emerge center around issues of choice, fluidity of identity, the phenomena of “coming out” and “passing,” and limitations to citizenship attendant to in/visible identities. Disability studies can provide a non-normative discursive space within which such identity issues may be addressed critically. Further, this article hopes to interject a bisexual perspective in discussions concerning applications of queer theory in disability studies.
Keywords: bisexuality; invisibility; intersectionality; identity; citizenship